The Impact of Vlogging and Podcasting on Iraqi EFL Learners’ Oral Proficiency and Willingness to Communicate - Nagam Hasan Hussein; Parviz Alavinia (Journal of Modern Research in English Language Studies, 2025)
The current study probed the effect of podcasting and vlogging on Iraqi EFL learners’ oral proficiency and willingness to communicate (WTC). In so doing, the participants’ perceptions concerning the efficacy of these technological resources for improving their spoken proficiency and WTC were also explored. Forty-five learners (in three intact classes) were selected from a language institute in Iraq through convenience sampling to conduct the study. Successive to administering the oral proficiency and WTC scales, the researchers initiated the intervention, which lasted for 14 sessions, with the classes being held twice a week. After holding the posttest, and at the culmination of quantitative phase of the study, 14 participants (seven students from each experimental group) were selected to take part in a semi-structured interview. The data collected for the quantitative phase were analyzed using one-way analysis of variance (ANOVA) and as regards the qualitative phase, thematic analysis was employed. The results demonstrated that both podcasting and vlogging groups gained better speaking scores on the posttest and exhibited higher degrees of WTC in comparison to the control group. The qualitative analysis indicated that the participants had positive attitudes toward using podcasting and vlogging to improve their oral proficiency. The findings are thought to have practical implications for teachers, learners, and other educational stakeholders in the context of Iraqi institutes, particularly as regards the proper integration of technology into language learning process.